HELIOTROPIC COMPASSES: THE SENTIMENTAL DREAM OF THE SOUTH IN THE POETRY OF MAXIMILIAN VOLOSHIN AND NIKOLAI GUMILEV (Journal of Contemporary Philology, 2024)
The South is a profound odeoporic, symbolic, archetypal, and sentimental theme in the verses of Maximilian Voloshin and Nikolai Gumilev – two classical and eccentric figures in the literary and historical period of the Silver Age of Russian poetry. This article illuminates the mysticism of the South and delves into understanding the symbols of the Sun and the Sea, while exploring the fascination with African culture and nature in the verses of Gumilev and the enchantment with the historical and natural treasures of the Mediterranean in the topographical poetry of Voloshin. The article explores the essential roles of wanderlust, Otherness, the boundaries between physical and imaginary geography, romantic escapism, and the phenomenological understanding of the chronotopic determinant of the South as a metaphysical metonymy of Baudelaire’s Unknown. Consequently, this thematic interpretation sheds light on the strong currents of the geographical imagination in the poetry of Voloshin and Gumilev, which epitomize the idea of the South as a miraculous myth.
Keywords: South; traveling; exoticism; chronotope; geographical imagination